2015
DOI: 10.1017/s1368980015001421
|View full text |Cite
|
Sign up to set email alerts
|

The Danish Organic Action Plan 2020: assessment method and baseline status of organic procurement in public kitchens

Abstract: Objective: With political support from the Danish Organic Action Plan 2020, organic public procurement in Denmark is expected to increase. In order to evaluate changes in organic food procurement in Danish public kitchens, reliable methods are needed. The present study aimed to compare organic food procurement measurements by two methods and to collect and discuss baseline organic food procurement measurements from public kitchens participating in the Danish Organic Action Plan 2020. Design: Comparison study m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 24 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…The extent of organic food conversion was defined as the proportion of food estimated to be organic by the kitchen workers. During the organic food conversion, public kitchens mainly applied the official Danish Organic Cuisine Label method 8,20 to register the proportion of organic food within one of the four intervals: 0-30% (no label), 30-60% (bronze label), 60-90% (silver label) and 90-100% (gold label). The amount of processed food products was also measured as a possible indicator of the conversion process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extent of organic food conversion was defined as the proportion of food estimated to be organic by the kitchen workers. During the organic food conversion, public kitchens mainly applied the official Danish Organic Cuisine Label method 8,20 to register the proportion of organic food within one of the four intervals: 0-30% (no label), 30-60% (bronze label), 60-90% (silver label) and 90-100% (gold label). The amount of processed food products was also measured as a possible indicator of the conversion process.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies are effectively implemented to cover the price premium of organic food and are also strongly linked to increased sustainability. 7,8,22 Moreover, Danish public kitchens spent 400 million DDK ($53.6 million Euro) on organic food procurement in 2013. 23 With the potential to increase the demand for organic produce, organic food conversion may impact environmental sustainability in terms of soil quality, water conservation, biodiversity, limiting application of antibacterial regimes and greenhouse gas emissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is based on procurement invoices over a period of three months from suppliers to calculate the organic food percentage in either monetary value or weight ( 21 ) . More detailed description of the calculation method can be found elsewhere ( 22 ) . Some kitchens, especially at baseline, were however not able to apply the Organic Cuisine Label method and hence the Dogme method was accepted ( 23 ) .…”
Section: Methodsmentioning
confidence: 99%
“…1-year follow-up, due to the fact that is is based on self-reported 364 information, opening up for potential recall bias especially among the non-certified 365 kitchens. A previous study has shown how self-reported estimations of the organic food percentage by public kitchens who do not apply the calculation method behind the 367 Organic Cuisine Label tend to be overestimated(Sørensen et al, 2015). Certified public 368 kitchens may also have an easier time recalling their exact current organic food 369 percentage compared with non-certified public kitchens due to the calculation sheet 370 exercises they complete on a regular basis to fulfil Organic Cuisine Label requirements.…”
mentioning
confidence: 99%